Challenges in Implementing Subject Specialisation by Primary Teachers in Zimbabwe - Majoni, Cuthbert (IJRDO- Journal of Educational Research, 2016)
The study aimed at investigating challenges faced by teachers in implementing subjectspecialisation in primary schools in Zimbabwe. A case study design was used and primaryschools in Bindura Primary Schools which have which apply subject specialisation wereconveniently selected. Data were generated through interviews open-ended questionnaires.Data were qualitatively analysed. The study found out that there was more of subject sharingthan subject specialisation since teachers were teaching subjects they did not specialise in.The study concluded that subject specialisation is relevant in primary school teaching andlearning an appropriate model should be designed to ensure its effectiveness. The studyrecommended that an appropriate model be designed to ensure subject specialisation isapplied effectively in schools.